The Influence of Individual Characteristics and Workload on Employee Performance through the Work Environment at the Ministry of Communication and Information Technology - Sara Rastina; Imam Wibowo; Tatag Herbayu Latukismo (Madani Connection, 2025)
This study aims to analyze the effect of individual characteristics and workload on employee performance with the work environment as a mediating variable at the Ministry of Communication and Information Technology. The study uses a quantitative approach with a survey method of employees of the Directorate General of Information and Communication Technology. Data analysis techniques use path analysis. The results show that individual characteristics and workload have a significant effect on the work environment. Individual characteristics and the work environment have a positive effect on employee performance. The work environment is proven to mediate the influence of individual characteristics and workload on employee performance. These findings emphasize the importance of individual suitability, job demands, and the organizational environment in improving the performance of public sector employees.